2012
DOI: 10.1158/1078-0432.ccr-12-0411
|View full text |Cite
|
Sign up to set email alerts
|

Vandetanib for the Treatment of Symptomatic or Progressive Medullary Thyroid Cancer in Patients with Unresectable Locally Advanced or Metastatic Disease: U.S. Food and Drug Administration Drug Approval Summary

Abstract: On April 6, 2011, the U.S. Food and Drug Administration approved vandetanib (Caprelsa tablets; AstraZeneca Pharmaceuticals LP) for the treatment of symptomatic or progressive medullary thyroid cancer in patients with unresectable, locally advanced, or metastatic disease. Vandetanib is the first drug approved for this indication, and this article focuses on the basis of approval. Approval was based on the results of a double-blind trial conducted in patients with medullary thyroid carcinoma. Patients were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(79 citation statements)
references
References 27 publications
1
70
0
6
Order By: Relevance
“…In this study, we used a large retrospective series of well-characterized MTC patients to define the expression of TKI target proteins in relation to specific clinical and tumor characteristics to provide data that could be used for rational selection of patients for TKI treatment. So far, vandetanib and cabozantinib, which have markedly improved the progression-free survival of MTC patients (Schoffski et al 2013, Thornton et al 2012, are the only agents that have been approved for the treatment of this disease, but a wide variety of additional multitargeted kinase inhibitors have entered clinical trials and several have shown clinical benefit in MTC patients. Promising results have been obtained with agents that primarily target angiogenesis and inhibit VEGF receptors at nanomolar concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a large retrospective series of well-characterized MTC patients to define the expression of TKI target proteins in relation to specific clinical and tumor characteristics to provide data that could be used for rational selection of patients for TKI treatment. So far, vandetanib and cabozantinib, which have markedly improved the progression-free survival of MTC patients (Schoffski et al 2013, Thornton et al 2012, are the only agents that have been approved for the treatment of this disease, but a wide variety of additional multitargeted kinase inhibitors have entered clinical trials and several have shown clinical benefit in MTC patients. Promising results have been obtained with agents that primarily target angiogenesis and inhibit VEGF receptors at nanomolar concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular therapy with inhibitors of mitogenic kinases has been disappointing, because it has not substantially improved the survival of patients with aggressive thyroid cancers, while showing an adverse sideeffect profile (Gild et al 2011). For instance, the multikinase inhibitor vandetanib, which has been approved for the treatment of inoperable or metastatic MTC (Thornton et al 2012), has shown a modest efficacy toward MTC progression, but an extremely toxic profile that includes gastrointestinal, cardiovascular, and neurological disorders (Chau & Haddad 2013). Similarly, the results of a phase II clinical trials on the efficacy of the mammalian target of rapamycin (mTOR) inhibitor everolimus for the treatment of locally advanced or metastatic thyroid cancer have been disappointing (Lim et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[8] Adverse effects: Diarrhea, colitis, hypertension and hypertensive crisis, fatigue, hypocalcemia, rash, and QT interval prolongation. [31] Sunitinib Sunitinib inhibits receptor tyrosine kinase which is responsible for the proliferation and angiogenesis of the cells of the tumor. It has multiple targets, and its inhibiting mechanism involves VEGFR-1, 2, and 3, PDGFR-a and -b, stem cell factor receptor (Kit), and fms-like tyrosine kinase Flowchart 2: Possible advantages and mechanisms using antiangiogenic therapies to enhance tumor response to radiation.…”
Section: Vandetanib (Zd6474 Zactima)mentioning
confidence: 99%